A cell-based scrambling assay reveals the phospholipid headgroup preference of TMEM16F on the plasma membrane - Chin Fen Teo; Sami T. Tuomivaara; Niek van Hilten; David Crottès; Yuh Nung Jan; Michael Grabe; Lily Y. Jan (Proceedings of the National Academy of Sciences, 2025)
The asymmetric resting distribution of the three major phospholipid classes on the mammalian plasma membrane, with phosphatidylserine and phosphatidylethanolamine mostly on the inner leaflet and phosphatidylcholine mostly on the outer leaflet, is maintained by ATP-dependent flippases and floppases that exhibit headgroup selectivity. Upon signaling cues, this asymmetry can be dissipated by various phospholipid scramblases, allowing cells to respond to stimuli and adapt to different physiological contexts. The prevailing view in the field is that phospholipid scramblases on the plasma membrane act without headgroup preference. Here, we report contrary experimental evidence based on a phospholipid scrambling assay that quantifies the fluorescence polarization (FP) of nitrobenzoxadiazole (NBD)-labeled phospholipids for kinetic monitoring of phospholipid scrambling on the plasma membrane of living cells. Our experiments reveal that the plasma membrane-residing calcium-activated phospholipid scramblase TMEM16F preferentially acts on phosphatidylserine and phosphatidylcholine over phosphatidylethanolamine.